Distribution of household labor between mothers and fathers in rural and urban Malaysia - Hossain, Ziarat; Madon, Zainal (University Of Toronto Press, 2022)
This study examined whether the distribution of household labor including childcare in Malay families varied as a function of the gender of parents and their rural-urban residence. Using a convenience-sampling approach, we interviewed mothers and fathers from 50 rural and 50 urban intact Malay families in peninsular Malaysia. We employed the tenets of the bioecological systems theory to interpret the findings. Multivariate analysis of variance revealed that mothers spent more time doing housework, laundry, childcare, and preparing meals than fathers did and fathers spent more time in maintenance and shopping for food than mothers did in both rural and urban families. Whereas urban fathers spent more time in childcare and shopping for food than their rural counterparts did, mothers and fathers in urban families equally participated in keeping track of expenses. The discrepancy between mothers’ and fathers’ time engagement in childcare was less in urban families than it was in rural families. Mothers were more engaged in traditional areas of household labor than fathers and compared to rural fathers, urban fathers spent more time in most household tasks including childcare. In view of rapid urbanization and multiethnic social context, the current findings are important because they highlight the contemporary patterns of parental engagement in household labor including childcare in understudied Malay families.